Answer:
x = -1 + 2 i or x = -1 - 2 i
Explanation:
Solve for x:
3 (x^2 + 5) = -6 x
Expand out terms of the left hand side:
3 x^2 + 15 = -6 x
Add 6 x to both sides:
3 x^2 + 6 x + 15 = 0
Divide both sides by 3:
x^2 + 2 x + 5 = 0
Subtract 5 from both sides:
x^2 + 2 x = -5
Add 1 to both sides:
x^2 + 2 x + 1 = -4
Write the left hand side as a square:
(x + 1)^2 = -4
Take the square root of both sides:
x + 1 = 2 i or x + 1 = -2 i
Subtract 1 from both sides:
x = -1 + 2 i or x + 1 = -2 i
Subtract 1 from both sides:
Answer: x = -1 + 2 i or x = -1 - 2 i